Nizhāmu Ta'limi al-Lughati al-'Arabiyyati wa Taqyimihi bi Thariqati al-Ikhtibār al-Mu'tamad 'ala al-Kumbiyutari (CBT) li Talamidz ash-Shaff ath-Thamin bi Madrasah Ma'arif Al-Mutawassithat Ghundang wa Tumalang wa Wunusubu - Kultsum Qothrotul Muna, Umi; Rizqi, Soffan; Faturrokhman, Faturrokhman (DAS Institute, 2024)
The aim of this Thesis is to: Explore the process of teaching Arabic language at MTs Ma’arif Gondang. Analyze the implementation of learning evaluation using Computer-Based Test (CBT). Identify the advantages and disadvantages of using Arabic teaching methods integrated with CBT-based evaluation. The results showed that the Arabic language teaching process in the school followed a structured and effective system that aligns with the nature of the material and linguistic skills, enhancing students' motivation to learn. The learning evaluation through CBT, implemented over the past three years, provided various conveniences for both teachers and students, and improved assessment efficiency. Its advantages include improving digital skills, saving time and cost, and ease of question storage, while its drawbacks include limited device availability, internet dependency, technical issues, and the potential for cheating during exams